Heart rate – a novel target for treatment of peripartum cardiomyopathy? - Imamdin, Aqeela; Lecour, Sandrine; Opie, Lionel H.; Sliwa, Karen; Azibani, Feriel (SA Heart Journal, 2017)
During pregnancy, heart rate (HR) is physiologically elevated but recovery occurs within 4 weeks of delivery. Peripartum cardiomyopathy (PPCM) is an acute condition which manifests with symptoms of heart failure late during pregnancy, or within 6 months of delivery. One of its main symptoms is elevated HR. Current standard therapy for PPCM makes use of diuretics, ACE inhibitors and beta-blockers. This approach does not satisfactorily improve HR in patients, even after 6 months of treatment. Strong evidence from both experimental and clinical studies suggests that modulation of the sino-atrial node with drugs such as ivabradine may benefi t patients suffering from PPCM. The activity of ivabradine is likely two-fold – direct with regards to heart rate and indirect with long-term structural changes affecting the heart itself, as well as the vascular and endogenous physiological systems. Large clinical trials are needed to validate this concept and further exploration of this hypothesis in an established rodent model of PPCM is required to investigate the outcome on both HR and its effects on other observable systems affected by PPCM.